El ratoncito, la fresa roja y madura, y el gran oso hambriento - Wood, Don, 1945-; Wood, Audrey; Mlawer, Teresa (New York : Scholastic, 2002)
A little mouse is determined to keep a big hungry bear from eating the strawberry he has picked with much effort.
Translation of: The little mouse, the red ripe strawberry, and the big hungry bear.
"This edition is only available for distribution through the school market"--P. [4] of cover.
AD570L
Accelerated Reader AR
Accelerated Reader
Keywords: Mice -- Fiction; Strawberries -- Fiction; Spanish language materials -- Juvenile fiction; Picture books